Comparison of post and iris substrate integrated waveguide band-pass filters for X-Band applications - Bandar, Hamman; Tokan, Nurhan Turker (YILDIZ TECHNICAL UNIV, 2022)
Me substrate integrated waveguide (SIW) has been proposed as a reliable alternative to the rectangular waveguide due to its small size, low cost, high performance, ease of manufacturing and simplicity of integration with other microwave components. This paper focuses on SIW band-pass filters and presents their design procedure in details. The methodology is applied to post and iris SIW filters working at X-band with different orders, responses and bandwidths. Two prototypes of third-order post and iris SIW filters are fabricated and measured with a vector network analyzer. The filters are designed to work at 10 GHz center frequency and 500 MHz bandwidth. The simulation results and measurement results of the post and iris SIW filters are compared. In the simulations lower than 0.9 dB insertion loss and better than 20 dB return loss is observed in the pass-band of the filters. The post filter exhibits lower insertion loss and higher reflection loss at the stop-band of the filter. With their low cost, small size, ease of manufacturing, high performance and integrability with other components, both of the demonstrated X-band SIW filters are very versatile and well suited for a variety of market applications, including radars and satellite communications.
Keywords: Band-pass filter; Centered post filter; Iris filter; SIW; DESIGN; CHEBYSHEV; CIRCUITS; LOSSES; Engineering